2018
DOI: 10.1111/bju.14470
|View full text |Cite
|
Sign up to set email alerts
|

Urine cytology is a feasible tool for assessing erythematous bladder lesions after bacille Calmette‐Guérin (BCG) treatment

Abstract: Bladder lesions after BCG instillations pose a challenge during follow-up and the appropriate management strategy is not clear. Lesions should not be overlooked as being BCG-induced irritation because they may harbour significant malignancies. The presence of papillary or flat tumour always warrants a biopsy or resection. In the case of erythematous lesions, our results suggest that biopsy may be avoided if voided urine cytology is negative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In that publication, slightly lower sensitivity and specificity values, 39% and 77%, respectively, were reported. 18 Guy et al included 130 patients, and both sensitivity (56%) and specificity (92%) of post-BCG cytology were reported. 24 Notably, neither investigation applied the TPS classification system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In that publication, slightly lower sensitivity and specificity values, 39% and 77%, respectively, were reported. 18 Guy et al included 130 patients, and both sensitivity (56%) and specificity (92%) of post-BCG cytology were reported. 24 Notably, neither investigation applied the TPS classification system.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Previous studies investigating the diagnostic accuracy of post-BCG cytology demonstrated wide variation in sensitivity, ranging from 33% to 67%. 17,18 However, none of those studies consistently used the TPS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these cases, and in patients who have received pelvic irradiation or intravesical therapies, UC has an important role in differentiating non-malignant erythematous urothelium (identified commonly as "red patches" on surveillance cystoscopy) from malignant urothelium/tumour recurrence. 5,9 UC is beneficial if it was positive at initial presentation; in such cases, it can provide confidence to the clinician and reassurance to the patient during surveillance if it remains negative/ benign, or prompts further investigation if it becomes suspicious/malignant. However, as an adjunct to diagnosis in suspected bladder cancer, the value of UC is less clear, mainly when it is performed on all haematuria patients, not just in those in whom bladder (or upper tract) cancer is suspected.…”
Section: Discussionmentioning
confidence: 99%
“…Although atypical UC was not associated with cancer, similarly to previous reports, our data highlighted the strong association of C4 and C5 cytology with high-risk tumours, and tumours that recurred over the follow-up period. 9,14 One could therefore suggest that patients with C4 or C5 cytology could or should be prioritised for TURBT or nephroureterectomy; however, even in cases where we attempted this, waiting times for TURBT were seldom reduced by more than a week, and it is difficult to estimate any potential beneficial effect this may have had on the patient or oncological outcomes.…”
Section: Discussionmentioning
confidence: 99%